First Metatarsophalangeal Joint Arthrodesis Using Flat Cut Technique and Fixing With Staples: A Review of Outcome (Medical Forum Monthly, 2020)
Objective: First metatarsophalangeal joint (MTPJ) arthrodesis is a gold standard procedure for advanced arthritis of the first MTPJ. The purpose of this study is to determine clinical, radiological, functional outcomes and complications of first MTPJ arthrodesis using flat on flat cut and fixing with two Shape-Memory Nitinol staples.Study Design: Retrospective studyPlace and Duration of Study: This study was conducted at the Department of Trauma and Orthopaedics Surgery, Solihull hospital, part of the University Hospitals Birmingham, UK from 2014 to 2018.Materials and Methods: Patients who underwent first MTPJ arthrodesis for primary osteoarthritis by the single surgeon (main author) from 2014 to 2018 were selected for the study. Preoperative and post-operative clinical and radiological findings, AOFAS Foot and Hallux scores, patient satisfaction rating and any complications were noted.Results: Thirty fivepatients, 37 feet, 2 patients had bilateral foot surgery at two different occasions, were found after the selection and exclusion criteria. 22 (63%) females and 13 (37%) males. Mean age was 63 years (range 35-8). The mean follow up of was 11 weeks (range 8-32 weeks). Union occurred in 33 cases including 3 cases of delayed union. 4 cases developed non-union, of these, 1 case was infective non-union. Average improvement in AOFAS score was 45(23-70). 42 (70%) of patient rated their outcome as Excellent, 14(20%) as good, 2(5 %) as fair and 2 (5%) rated as poor.Conclusion: First MTPJ arthrodesis using Shape-Memory Nitinol staples resulted in 89% union rate. Patients had average of improvement 44 points on AOFAS score and 90% rated good to excellent satisfaction. These results are comparable with national average results.